Critical appraisal of diagnostic studies in nuclear medicine - Marienhagen, J.; Eilles, Ch. (Nuklearmedizin - NuclearMedicine, 2003)
The conceptual ideas of evidence based critical appraisal of diagnostic studies are described in this survey. In this context special attention is given to biases in study design such as verification- as well as information-bias limiting the validity of diagnostic studies. The practice of critical appraisal is demonstrated in an application to an example of a nuclear medicine scenario. The impact of evidence based medicine on nuclear medicine as a diagnostic discipline is discussed in detail.
Keywords: Evidence based medicine; diagnostic studies; likelihood ratio; bias; STARD-initiative